Morphological description of the immature stages of Hermetia illucens (Linnaeus, 1758) (Diptera: Stratiomyidae) - Barros, Luana Machado; Gutjahr, Ana Lúcia Nunes; Ferreira-Keppler, Ruth Leila; Martins, Renato Tavares (Microscopy Research and Technique, 2019)
In the dipteran genus Hermetia, only 6 of the 78 valid species have documented immature stages: H. albitarsis Fabricius, 1805, H. aurata Bellardi, 1859, H. concinna Williston, 1900, H. illucens (Linnaeus, 1758), H. panamensis Greene, 1940 and H. pulchra Weidemann, 1830. In particular, H. illucens stands out due to its reported applicability for forensic, medical and economic purposes. Here, we described the morphology of eggs and immature stages of this species, with a view to detecting differences between instars and in the pupal stage, which should eventually help properly identifying larval age. We utilized both optical and scanning electron microscopy tools. The eggs are elliptical and elongated, and color varies from cream white to yellowish. The larvae are apodal, hemichephalic and holopneustic, flattened dorso-ventrally and may be recognized by the head elongated, dorsal and ventral chaetotaxy of the cephalic capsule, thoracic and abdominal segments, and the morphology of the anterior and posterior spiracles. The pupae are adecticous and coarctate, tegument dark brown and pruinescence varying from brown to golden. The overall morphology across instars is similar, but marked variations were observed in the shape of the antennal articuli and the shape of the setae (first instar compared to the others). Our results supplement the biological information on Hermetia illucens and should aid the proper identification and aging of juveniles in the field, as a way to minimize errors in the calculation of the post-mortem interval. © 2018 Wiley Periodicals, Inc.
Keywords: Anatomy And Histology; Animals; Cytology; Diptera; Embryology; Larva; Ovum; Pupa; Microscopy, Electron, Scanning; Animal; Diptera; Larva; Microscopy, Electron, Scanning; Ovum; Pupa